The relationship between soil properties in pedogenesis dynamics: A study of pedons on slopes and basins - Henly Yulina; Mahfud Arifin; Rina Devnita; Muhamad Rahman Djuwansah; Fatharani Raidasari (Universitas Sebelas Maret, 2025)
Soil formation and weathering are essential processes influencing natural fertility, yet the combined role of particle size distribution, texture, and organic carbon content at the profile scale remains understudied. Earlier research has focused chiefly on soil properties at the landform or regional scale, without examining interhorizon variations, leading to a limited understanding of their interactions in pedogenesis under different environments. This study compared the physical and chemical characteristics of soils in two contrasting pedons, Jatinangor (slope) and Tanjungsari (depression), both located in Sumedang Regency, West Java, Indonesia, with similar soil-forming factors. A descriptive-comparative method was employed using horizon-based sampling, laboratory analysis, and Principal Component Analysis (PCA) to reveal relationships and dominant factors. Results indicated that clay fractions dominated the JTN (Jatinangor) pedon with a clay texture due to intensive weathering under well-drained conditions. In contrast, the TJN (Tanjungsari) pedon was dominated by silt fractions resulting from fine material deposition under waterlogged conditions. Organic carbon content was lower in JTN due to leaching on slopes, whereas higher accumulation occurred in TJN due to depression settings. PCA identified sand fraction as the main discriminating factor, while fine fractions (silt and clay) were positively associated with organic carbon. These findings highlight that integrated analysis of these variables at the pedon scale provides a sensitive indicator of pedogenesis, weathering, and soil fertility.